Dampak Pengembangan Komoditi Nilam terhadap Kesejahteraan Masyarakat Kabupaten Nagan Raya - Frici Manza Hernisa; Okta Rabiana Risma (Universitas Teuku Umar, 2022)
In this study, the purpose of the research was to see the development anda development of patchouli on the welfare of the commonity. This research was conducted in Ujong Blang Village and Blang Baro Rambong Village, Beutong District, Nagan Raya Regency. The problem is with the develpoment of patchuli , it is hoped that is can improve the commodity’s economy because there is still a large area of abandonedland with fertile soil being one of the very good potentials for patchuoli. In this study, researchers used qualitative methods, which collected data through primary and secondary data. The method used in descriptive method. Secondary data was obtained from the regional development planning agency and primary data was obtained by direct interviews with patchuoli farmers. The respondent in this study consisted of internal. Parties, namely the Village head of Ujong Blang Village and Blang Baro Rambong Village. External parties, namery the head of the economy development planning division of the regional development planning agency of Nagan Raya Regency. Basd of the result of research on the development of the patchuoli commodity on the welfare of the commodity, the benefits can a better standard of living.